2012
DOI: 10.1111/j.1365-2702.2012.04145.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress and stressors in the clinical environment: a comparative study of fourth‐year student nurses and newly qualified general nurses in Ireland

Abstract: Aims and objectives.  To measure and compare the perceived levels of job‐related stress and stressors of newly qualified nurses and fourth‐year student nurses in the clinical environment and to explore the participants’ views on stress and stressors. Background.  Stress in the nursing workplace has significant consequences for the person, the patient and the organisation, such as psychological and physical health deterioration and impaired professional practice. To address this problem, stress and stressors ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 146 publications
(400 reference statements)
4
86
1
1
Order By: Relevance
“…However, it is difficult for fresh nursing graduates to communicate with doctors, senior nurses, patients, and relatives. This finding is consistent with Casey et al, [12] Parker et al [3] and Suresh et al [8] They are hesitant to speak up because they have less prior experience of communication with others except nurses when they were student nurses. In addition, the superior-inferior relationship with doctors and senior nurses and the blame and complaint culture in hospitals also obstruct effective communication.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…However, it is difficult for fresh nursing graduates to communicate with doctors, senior nurses, patients, and relatives. This finding is consistent with Casey et al, [12] Parker et al [3] and Suresh et al [8] They are hesitant to speak up because they have less prior experience of communication with others except nurses when they were student nurses. In addition, the superior-inferior relationship with doctors and senior nurses and the blame and complaint culture in hospitals also obstruct effective communication.…”
Section: Discussionsupporting
confidence: 82%
“…Their stress as qualified nurses comes from excessive workload in the ward. [7,8] They also express challenges in managing and prioritizing routine work and heavy workloads in the first few months. [3,6] Another study showed that the nurses working in general medical or surgical wards have high stress levels due to heavy workloads.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep disorders comprise the factor that is specifically highlighted with respect to healthcare workers (Poissonnet & Véron, 2000;Rose & Glass, 2009), especially considering the effects of night shift-work and difficult work schedules. Some authors underlined the role of leisure activities and other off-job experiences in buffering the negative effects of the reported factors (Tuisku et al, 2016), since an improved general quality of life may positively affect employee well-being (Preposi Cruz, 2016 d 'Ettorre & Greco, 2016;Einarsen & Matthiesen, 1998;Estrynbehar et al, 1990;Galletta et al, 2016;Jakobsen et al, 2015;Markwell & Wainer, 2009;McVicar, 2003;Niedl, 1996;Nixon et al, 2015;Park et al, 2004;Salmond & Ropis, 2005;Sun et al, 2016;Suresh et al, 2013;A. Yildirim & D. Yildirim, 2007) highlighted the relevance of mobbing, conflicts, lack of rewards and recognition by superiors, work demands, work duration, difficulty in balancing work and family commitments, and work context factors.…”
Section: Interpreting the Findingsmentioning
confidence: 99%